ANALISA PERAN MODERASI AUDIT TENURE DALAM HUBUNGAN ANTARA ORIENTASI KESALAHAN INDIVIDU DAN IKLIM KESALAHAN ORGANISASI TERHADAP PENANGANAN KESALAHAN PADA AUDITOR INSPEKTORAT KEMENTERIAN DI INDONESIA - Mintoyuwono, Danang (Department of Accounting, Faculty of Economics and Business, Universitas Pembangunan Nasional Veteran Jakarta, 2015)
The auditor’s error handling strategy as auditor behavior after detecting an auditee’s error has significant impact on repeat error finding especially unintentional errors. The purpose of this study was to investigate factor determining error management as auditor error handling strategy from organizational and individual aspect also investigate moderation role of audit tenure. 103 government auditor involve in this study as respondent collecting via convenience sampling, with linear regression and interaction moderated regression as data analysis method. Result of this study shows both organizations’ error climate and person’s individual error orientation has positive significant impact on error management as auditor error handling strategy otherwise moderation of audit tenure have no empirical evidence. Thus error management is conducting by auditor in an open climate organization with greater person’s individualerror orientation.